The MADS-box protein SHATTERPROOF 2 regulates TAA1 expression in the gynoecium valve margins - Verma, Subodh; Švihlová, Lenka; Robert, Hélène S (Plant reproduction, 2025)
SHATTERPROOF 2 regulates TAA1 expression for the establishment of the gynoecium valve margins. Gynoecium development and patterning play a crucial role in determining the ultimate structure of the fruit and, thus, seed production. The MADS-box transcription factor SHATTERPROOF 2 (SHP2) contributes to valve margin differentiation and plays a major role in fruit dehiscence and seed dispersal. Despite the acknowledged contribution of auxin to gynoecium development, its precise role in valve margin establishment remains somewhat enigmatic. Our study addresses this gap by uncovering the role of SHP2 as a positive regulator of key auxin biosynthetic genes, TAA1 and YUCCA 4. Genetic and molecular analyses revealed that SHP2 directly regulates the expression of TAA1 in the valve margins of a stage 12 gynoecium with known regulators of flower and ovule development, such as AGAMOUS, SEEDSTICK, and SEPATALA 3. Collectively, our findings define a previously unrecognized function of SHP2 in the regulation of auxin biosynthetic genes during gynoecium development and raise the possibility that the auxin produced under SHP2 regulation may contribute significantly to the valve margin establishment.
Keywords: regulace genové exprese u rostlin; proteiny huseníčku; MADS Domain Proteins; Gynoecium; SHATTERPROOF 2; Valve margins; proteiny domény MADS; Arabidopsis Proteins; kyseliny indoloctové; YUCCA 4; Auxin; květy; Flowers; Indoleacetic Acids; Gene Expression Regulation, Plant; TAA1; Arabidopsis